Causes of death in patients with chronic kidney disease: insights from the ASCEND-D and ASCEND-ND cardiovascular outcomes trials. (3rd October 2022) - Singh, A K; Acharya, A; Carroll, K; Lopes, R D; McCausland, F R; Mulloy, L; Perkovic, V; Solomon, S; Waikar, S S; Wanner, C; Wong, M G; Cobitz, A R; et al.
Abstract: Background: There are limited contemporary data available regarding adjudicated causes of death in patients with chronic kidney disease (CKD). Prior studies have indicated that cardiovascular (CV) events are one of the most common causes of death among patients with CKD, with previous reports stating approximately 30% of patients died from CV causes [1]. Here, we report the adjudicated causes of death in two recently completed large-scale randomised controlled trials (RCTs) with ∼14, 200 person years of follow-up: ASCEND-D [2] (median follow-up: 2.5 years; NCT02879305) and ASCEND-ND [3] (median follow-up: 1.9 years; NCT02876835). These trials investigated the safety and efficacy of daprodustat, a hypoxia-inducible factor prolyl hydroxylase inhibitor (HIF-PHI), in correcting anaemia in patients with CKD. Purpose: This study assessed the causes of death in patients with CKD in the ASCEND-D and ASCEND-ND trials. Methods: ASCEND-D and ASCEND-ND were global, randomised, open-label, CV outcome trials in adult patients with CKD-related anaemia undergoing maintenance dialysis (ASCEND-D) or with pre-dialysis CKD (ASCEND-ND) who received daily oral daprodustat or conventional erythropoiesis-stimulating agents (ESAs). Cause of death was systematically and centrally adjudicated in a blinded fashion to the study treatment assignment by an independent committee. Results: In ASCEND-D and ASCEND-ND, respectively, 2964 and 3872 patients were randomised, of which 92% and 97% completed the study. Baseline characteristics were well-balanced across treatment groups within each trial. Adjudicated causes of death for the ASCEND-D and -ND trials are shown in the Table. All-cause mortality was similar in patients treated with daprodustat as compared with those treated with conventional ESA in both the ASCEND-D and -ND trials. Overall mortality in the ASCEND-D and -ND trials was 20.0% and 15.5%, respectively, and CV causes accounted for approximately 30–40% of all deaths and infection accounted for 25–30% of all deaths in both trials. Conclusion: Although CV events were the most common cause of death in the ASCEND-D and ASCEND-ND trials (30–40% of cases), the risk of death due to infection was also high, accounting for approximately 25–30% of all deaths across all study arms. Sudden death accounted for most CV deaths, particularly in the ASCEND-D trial. Infection as a cause of death was more frequent than previously reported in other RCTs or disease registries. Causes of death did not differ significantly between ASCEND-D and ASCEND-ND, or between treatments. However, as this is a selected population for a CV trial, it may not be representative of a real-life CKD population. Our results provide important data to inform the design of future studies in this population. Funding Acknowledgement: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): This study was funded by GlaxoSmithKline. Medical writing support was provided Natasha Tracey, PhD (Ashfield MedComms, Macclesfield, UK) and was funded by GlaxoSmithKline.